HUBUNGAN ANTARA KUALITAS LABA, ASIMETRI INFORMASI, DAN BIAYA MODAL EKUITAS: PENGUJIAN MENGGUNAKAN ANALISIS JALURPADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2014-2016 - Isaura Tribuana Puteri, 14.05.52.0250; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2018)
This study examines the direct and indirect impacts of earnings quality on cost of equity capital by using path analysis. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange 2014-2016.Data were collected using purposive sampling method of the companies listed in the Indonesia Stock Exchange.(1) The results of the study found that earnings quality had a not significant positive effect on the cost of equity capital. These results indicate that the greater the value of earnings quality, the lower the cost of equity capital. (2) The results found that earnings quality had a significant negative effect on information asymmetry. These results indicate that a company that has low earnings quality, the information asymmetry of the company is higher. (3)The results of the study found that information asymmetry had a not significant positive effect on the cost of equity capital. These results indicate that the size of earnings management behavior does not determine the increase in the cost of equity capital. (4) The results of the study did not find a direct influence but the researchers managed to find the indirect effect of earnings quality as measured by discretionary accruals on the cost of equity capital. Keyword: earnings quality, information asymmetry ,cost of equitycapital, discretionary accrual